Effect of Calcination Temperature on the Pozzolanic Activity of Brazilian Sugar Cane Bagasse Ash (SCBA) - Ribeiro,Daniel Véras (2014)
This study evaluated the feasibility of using sugar cane bagasse ash (SCBA), a by-product of the sugar cane ethanol industry, obtained under controlled calcination as a partial replacement for Portland cement in mortars. Materials with pozzolanic characteristics may be used to partially replace cement in mortars or concrete and are known to provide durability to the products. Initially, TG/DTA curves of the sugar cane bagasse were conducted to define suitable calcination temperatures (500ºC, 600ºC and 700ºC), and tests were conducted to characterize the physical-chemical parameters of the SCBA and the pozzolanic activity according to NP EN 196-5. The results showed the technical feasibility of using the SCBA as a pozzolanic material in construction, which would provide an alternative to proper disposal for this waste while providing products with high technical performance.